ChemInform Abstract: Structurally Diverse Hamigerans from the New Zealand Marine Sponge Hamigera tarangaensis: NMR‐Directed Isolation, Structure Elucidation and Antifungal Activity. Issue 15 (15th April 2014) - Singh, A. Jonathan; Dattelbaum, Jonathan D.; Field, Jessica J.; Smart, Zlatka; Woolly, Ethan F.; Barber, Jacqueline M.; Heathcott, Rosemary; Miller, John H.; Northcote, Peter T.
Abstract All new hamigerans exhibit micromolar activitiy towards the promyelocytic leukaemic cell line HL60.